ANALYSIS OF THE PRODUCT DISTRIBUTION MECHANISM AT THE DISTRIBUTION CENTER OF NURUL JADID ISLAMIC ECONOMIC PERSPECTIVE AFZALUL ROHMAN - Muhammad Andreansyah Hidayatulloh (IJED: International Journal of Economy Development Research, 2024)
This This research will analyze the distribution mechanism at the Nurul Jadid Distribution Center from an Islamic Economics perspective according to Afzalur Rahman. The focus includes: (1) The distribution mechanism at the Nurul Jadid Islamic Boarding School, (2) Afzalul Rohman's Islamic Economics view of the distribution mechanism, and (3) Supporting and inhibiting factors in distribution at the center. The results of this research show that the center distribution mechanism namely: making customer levels,: retail stores, agents, distributors, creating their own products (Nurja mineral water, salt, atlas covers and BHS, providing education to customers on how to market in accordance with sharia principles, providing product information according to conditions. In discussing the application of the principles-Islamic economic principles by the Distribution Center (DC) based on the teachings of Afzalul Rahman. DC adopts the principle of Tauhid to realize the welfare of the country, the principle of Maslahah by prioritizing the common interests of Islamic boarding schools and society, and the principle of justice by providing equal services to all consumers. DC applies leadership principles by selecting leaders who understand Islamic principles. Implementation of these principles strengthens the integrity of the distribution system and supports social welfare. This factor assesses the factors supporting distribution efficiency in Distribution Centers (DC), namely effective leadership, adequate infrastructure, and good coordination. No inhibiting factors were found in the DC distribution system.